2004
DOI: 10.1016/j.jmb.2004.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization and Comparative Phylogenetic Analysis of Escherichia coli HemK, a Protein (N5)-glutamine Methyltransferase

Abstract: Protein glutamine methylation at GGQ sites of protein chain release factors plays a pivotal role in the termination of translation. We report here the crystal structure of the Escherichia coli HemK protein (N5)-glutamine methyltransferase (MTase) in a binary complex with the methyl-donor product S-adenosyl-L-homocysteine (AdoHcy). HemK contains two domains: a putative substrate binding domain at the N terminus consisting of a five helix bundle and a seven-stranded catalytic domain at the C terminus that harbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 53 publications
2
41
0
Order By: Relevance
“…The NPPY motif found in the active site of both glutamine-and adenine-specific methyltransferases makes major contacts with the target amide group in the substrate and the methyl donor AdoMet, in common to both types of the enzymes (27). This misidentification of N6amt1 resembles the case of Dnmt2, which was initially classified as a putative cyimmunopurified with anti-eRF1 polyclonal antibodies from transfected HEK-293T cells, separated, and in-gel digested with chymotrypsin prior to MALDI-TOF MS analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NPPY motif found in the active site of both glutamine-and adenine-specific methyltransferases makes major contacts with the target amide group in the substrate and the methyl donor AdoMet, in common to both types of the enzymes (27). This misidentification of N6amt1 resembles the case of Dnmt2, which was initially classified as a putative cyimmunopurified with anti-eRF1 polyclonal antibodies from transfected HEK-293T cells, separated, and in-gel digested with chymotrypsin prior to MALDI-TOF MS analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The murine N6amt1 gene consists of 6 exons that form two transcript isoforms with the first 4 exons in common (23). Proteins encoded by both isoforms contain the conserved GXGXG motif essential for the binding of AdoMet and the NPPY motif essential for the binding of an amide side chain (27). To ensure functional loss of the N6amt1 gene, exon 4 encoding the NPPY motif was replaced by a Neo gene through homologous recombination in embryonic stem (ES) cells (Fig.…”
Section: Identification Of Gln185 Methylation Of Erf1 In Hek-293t Cellsmentioning
confidence: 99%
“…1). Although overall sequence homology is relatively low, these proteins are highly homologous in the regions responsible for binding AdoMet (40), particularly motif I (44) with consensus sequence hh(D/E)hGXGXG (where h is a hydrophobic residue) and the NPPY motif, which were both previously thought to be characteristic of DNA methyltransferases (45)(46)(47). Multiple sequence alignments and phylogenic analysis demonstrated that E. coli PrmC and S. cerevisiae Mtq1p and Mtq2p, as well as their various orthologs, could be classified into two related subfamilies of protein methyltransferases (supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This led to the suggestion that HemK was itself an AdoMet-dependent DNA MTase (15), and its classification in data bases as "probable MTase modifying N6-adenine or N4-cytidine in DNA" including the renaming of many entries to N6AMT. However, no evidence could be found that HemK is able to methylate DNA (16,17). Later it was found that E. coli HemK methylates a glutamine residue in the ribosomal release factors (RF1 and RF2) at the universally conserved tripeptide GGQ motif (18,19), indicating that the alignment based assignment of HemK as an AdoMet dependent MTase was correct although the predicted substrate was wrong.…”
mentioning
confidence: 99%
“…The first structures of HemK MTases have been determined from Thermotoga maritima (23) and E. coli (16). Closely similar, the structures revealed two domains: an N-terminal domain with no significant similarity to MTase sequences other than close HemK homologs and a C-terminal domain that contains the (D/N/S)PP(Y/FW) motif and shows strong similarity to members of the family 7 ␤-strand methyltransferases (also referred as class I methyltransferases).…”
mentioning
confidence: 99%